The Health Services Federation of Great Britain (leaflet) (1938)
1938 1938 1930s 5 pages THE HEALTH SERVICES FEDERATION OF GREAT BRITAIN CENTRAL OFFICE:- 38, ARGYLE SQUARE, LONDON, W.C.1. Tel.: Terminus 1102/5. (All communications to be addressed to the General Secretary). 292/54.73/2/5